Epistemologi: positivisme, fenomologi, teori koherensi, korespondensi, pragmatis, intersubjektif - khoir, Zalifatul; Fahrezi, Dava Achmad; Azela, Imelda Nur (Maliki Interdisciplinary Journal, 2025)
Epistemology as a branch of philosophy concerned with the nature, sources, and validity of knowledge. It focuses on six major epistemological approaches: positivism, phenomenology, coherence theory, correspondence theory, pragmatism, and intersubjectivity. Each approach is analyzed in terms of its foundational principles, methods of acquiring knowledge, and implications for the development of science. Positivism emphasizes empirical facts; phenomenology centers on subjective experience; coherence theory evaluates truth through logical consistency; correspondence theory stresses alignment with reality; pragmatism views truth based on practical utility; and intersubjectivity highlights the role of communication and social consensus. The study underscores the essential role of epistemology in shaping the methodological foundations of science and fostering critical and reflective thinking in the philosophy of science.